Recycling electro-coagulated sludge from textile wastewater treatment plants as an adsorbent for the adsorptions of fluoride in an aqueous solution. Issue 6 (June 2021) - Aragaw, Tadele Assefa
Abstract: This research investigated the high content of iron-based materials from recycled electro-coagulated (EC) sludge for the adsorptive removal of fluoride, and the properties of the material were characterized. The thermal activation of EC sludge in which the unwanted impurity was removed by beneficiation and thermally activated at 500 °C, and was used for fluoride removal. Basic operating parameters (mixing time, adsorbent dosage, adsorbate concentration, solution pH, and temperature) were examined to evaluate the optimum de-fluoridation capacity (DC). The functional groups, the crystalline structure, and surface morphology of thermally treated and raw EC sludge were analyzed using FTIR, XRD, and SEM, respectively, and demonstrates that thermally activated EC sludge contains significant content of magnetite and hematite. The optimum DC was recorded as 5.12 mg of F − /gm with experimental conditions: mixing time = 20 min, adsorbent dosage = 0.3 gm/100 ml, initial fluoride concentration = 1 mg/L, and pH = 5 at the temperature of 353 K. The Langmuir isotherm model was fitted, and the capacity is calculated as 6.43 mg/g. The adsorption process follows the Pseudo-Second-order kinetic models. It can be concluded that the prepared adsorbents have excellent fluoride removal capacity, and EC sludge can be used as an alternative adsorbent for de-fluoridation. Highlights: Iron-based oxides and hydroxides from the EC sludge were recovered and prepared for fluoride ion adsorption. EC sludge as an iron-based adsorbent was synthesized by thermal activation at 500 °C. Iron oxide adsorbents could efficiently remove fluoride ions from synthetically prepared water solutions. The adsorption of fluoride followed a Langmuir isotherm pseudo-Second-order kinetic model. The prepared adsorbents were regenerated in an aqueous solution and the reusability efficiency was up to the 4th cycle. Abstract : EC sludge; Adsorption; Characterization; Defluoridation; Equilibrium.